Unintentional childhood injuries in urban Delhi: A community-based study - Giridara Gopal Parmeswaran; Mani Kalaivani; Sanjeev Kumar Gupta; Anil Kumar Goswami; Baridalyne Nongkynrih (Wolters Kluwer Medknow Publications, 2017)
Background: Childhood injuries claim around a million lives around the world each year. A community-based study on childhood injuries would provide valuable information on the epidemiology of injuries. Objective: To assess the prevalence of unintentional childhood injuries in an urban locality and determine various sociodemo graphic factors associated with childhood injuries. Methods: The study was done in urban Delhi among 1,639 children aged less than 18 years. Information on injuries in the last one year was collected. Only those injury episodes where treatment was sought or the child was left disabled after the injury were included. Treatment seeking behavior and the impact of injury on the child and the household were also assessed. Results: Among 1,639 children, 102 children suffered 116 episodes of various types of injuries in the last one year. Prevalence of injuries was 7.1% (95% CI: 5.9-8.4). Mean age was 8.5 ± 5.1 years. Prevalence was more in boys (8.4%) than girls (5.1%). Accidental falls (37.1%), dog bites (25%), and road traffic injuries (18.9%) were the three most common modes of injury. Two-thirds of children with injuries were taken to the emergency facility for treatment while 40% resorted to home remedies. Treatment expenses in some families led to the need for borrowing money, additional employment by another family member, and selling of household assets. Conclusions: The prevalence of childhood injuries in the past one year was 7.1%. Maximum injuries occurred at home and were mostly accidental falls and dog bites. Childhood injuries caused loss of school attendance and financial burden to the family.